Desmoglein-2 as a cancer modulator: friend or foe? - Myo Min, Kay K.; Ffrench, Charlie B.; McClure, Barbara J.; Ortiz, Michael; Dorward, Emma L.; Samuel, Michael S.; Ebert, Lisa M.; Mahoney, Mỹ G.; Bonder, Claudine S. (Frontiers in Oncology, 2023)
Desmoglein-2 (DSG2) is a calcium-binding single pass transmembrane glycoprotein and a member of the large cadherin family. Until recently, DSG2 was thought to only function as a cell adhesion protein embedded within desmosome junctions designed to enable cells to better tolerate mechanical stress. However, additional roles for DSG2 outside of desmosomes are continuing to emerge, particularly in cancer. Herein, we review the current literature on DSG2 in cancer and detail its impact on biological functions such as cell adhesion, proliferation, migration, invasion, intracellular signaling, extracellular vesicle release and vasculogenic mimicry. An increased understanding of the diverse repertoire of the biological functions of DSG2 holds promise to exploit this cell surface protein as a potential prognostic biomarker and/or target for better patient outcomes. This review explores the canonical and non-canonical functions of DSG2, as well as the context-dependent impacts of DSG2 in the realm of cancer.